2004
DOI: 10.1111/j.1651-2227.2004.tb00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Do inhaled steroids differ from cromones in terms of hospital admission rates for asthma in children?

Abstract: Aim: The aim of the present study was to investigate the characteristics of hospital admissions in two child populations receiving different types of drugs as their regular medication for steady‐state asthma. Methods: Annual data on children aged under 16 y treated for asthma, including consumption of regular medication for asthma, numbers of hospital periods, lengths of hospitalizations and annual proportions of readmissions, were collected using patient‐specific medical records from 1995 to 1999. In the Kuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In line with studies made in older children, [1,6,7,9] readmissions were less frequent in the area where maintenance therapy in young children was more active. In the present study in children less than 2 years old, active use of ICSs was observed in the Kuopio area, opposite to the previous fi ndings in older children [9] (Table 3). Thus, the different admission rates between these two hospitals indicate more probably differences in maintenance therapy than those in hospitalization practice.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In line with studies made in older children, [1,6,7,9] readmissions were less frequent in the area where maintenance therapy in young children was more active. In the present study in children less than 2 years old, active use of ICSs was observed in the Kuopio area, opposite to the previous fi ndings in older children [9] (Table 3). Thus, the different admission rates between these two hospitals indicate more probably differences in maintenance therapy than those in hospitalization practice.…”
Section: Discussionsupporting
confidence: 84%
“…[1,4,5] In particular, this improved asthma control has decreased the risk of repeated hospital admissions. [6][7][8] In our previous study in over 2-year-old children with asthma, hospitalizations were less common in the Oulu area where ICSs were in active use for asthma, compared with the Kuopio area with a step-wise use of cromones and ICSs [9] (Table 3). On the other hand, hospitalizations reveal only the top of the iceberg, and the true burden caused by mild asthma in the child population is unknown.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations